Empty Promises in Post-Apartheid South Africa: The inability of the labor and tenure legislation to protect South African farmwomen - Schuthof, Fiore (Student Undergraduate Research E-journal!, 2018)
In this study, it is shown that the post-apartheid labor and tenure legislation are unable to protect South African farmwomen. There is a tendency among scholars to attribute this weak legal position to the country’s legacy of colonialism and apartheid. This study proposes a different narrative, by focusing on the inclusive nature of post-apartheid legislation. It is the aim of this paper to examine to what extent the inability of this legislation to protect farmwomen can be explained by using an intersectional lens. This lens explores the effects of ‘rurality’ and gender on the legal position of farmwomen.